When Money Dies: The Dynamics of Speculative Hyperinflations - Rocheteau, Guillaume (American Economic Review, 2025)
How quickly does a fiat money become valueless? I study the speculative hyperinflation equilibria of continuous-time economies with decentralized markets where money is essential. I establish necessary and sufficient conditions under which money dies in finite time. A necessary condition is that the liquidity return of money grows unbounded as the value of money approaches zero. Under CRRA preferences, the longevity of money shrinks with the money growth rate and the frequency of liquidity needs, but it increases with seller’s market power. Money duration also depends on the strictness of legal restrictions and the rates of return of competing currencies. (JEL E31, E42, E51, E52, E62)